Maths
posted by Nat on .
I have a maths exam tomorrow and am studying with a friend. We are working on a question and are getting two different answers. Could you please show us the right way to do it?
2(4x + 3)(4x  3)  (4x + 3)squared
p.s i couldn't find a squared symbol so only the last bracket is squared, not the whole equation.

2(4x + 3)(4x  3)  (4x + 3)squared
we usually write it this way
2(4x + 3)(4x  3)  (4x + 3)^2
= 2(16x^2  9)  (4x + 3)(4x + 3)
= 2(16x^2  9)  (16x^2 + 24x + 9)
= 32x^2  18  16x^2  24x  9
= 16x^2 24x  27
or you could take out a common factor from
2(4x + 3)(4x  3)  (4x + 3)^2
= (4x + 3)(2(4x3)  (4x+3))
= (4x+3)(8x64x3)
= (4x+3)(4x9)
= 16x^2  36x + 12x  27
= 16x^2  24x  27
not saying the second way is any easier, just another way to show it